Polygonatum sibiricum Polysaccharides Extracted with Ultrasound-Assisted Deep Eutectic Solvents Protect L6 Cells Against Oxidative Stress in a Cellular Model of Sarcopenic Obesity - Sun, Chaoqun; Xu, Yifan; Du, Hanchen; Chen, Yan; Qu, Wenjie; He, Menglu; Liu, Zhengyi; Huang, Jian; Huo, Junsheng; Yin, Jiyong; Liu, Jing (Antioxidants, 2025)
Oxidative stress is closely associated with sarcopenia obesity (SO). As the primary active component of Polygonatum sibiricum, Polygonatum sibiricum polysaccharide (PsP) is recognized as a potent antioxidant and has become a focus of research for potential therapeutic strategies against SO. Our previous study demonstrated that ultrasound-assisted deep eutectic solvents (UAE-DESs) significantly improve the extraction efficiency of PsP; however, the antioxidant effect of PsP extracted using UAE-DESs was unexplored. This study investigated the effects of PsP extracted by UAE-DESs on an oxidative stress model in L6 cells induced by palmitic acid (PA). The results revealed that PsP enhanced the ability of L6 cells to resist PA-induced effects, including ectopic lipid deposition, changes in reactive oxygen species (ROS) levels, malondialdehyde (MDA) contents, and the activities of glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), and catalase (CAT). Additionally, PsP upregulated the expression of myosin heavy chain (MHC) and myoblast differentiation (MyoD) protein, while increasing myotube cell diameter. These findings suggested that PsP extracted by UAE-DESs can enhance the antioxidant capacity of L6 cells against PA-induced oxidative stress in a simulated SO model, providing a potential therapeutic agent for the prevention and treatment of SO.